Design and Build Minang Music Applications Based on Android - Dewi, Ika Parma; Kamil, Fadhil Muhammad; Ambiyar , Ambiyar; Refdinal, Refdinal; Indarta, Yose (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Minang music applications are rarely found in the play store. As for some regional music applications that already exist but have many shortcomings such as not having lyrics and some have no features other than playing songs. Based on the data collection, a music application was created which aims to create an application that is not only a music player but also has other features such as viewing lyrics, adjusting the equalizer, having a sleep time feature and a search feature. Minang music application is designed using the waterfall method. The waterfall method is carried out through a systematic approach. Starting from the system requirements stage then to the analysis, design, coding and testing stages. The first aspect is to conduct interview sessions with related communities that are faced when they want to listen to music. In addition, interviews were also conducted regarding what features the community wanted. The second aspect is to compare the existing application with the application to be designed. Later, the application designed to be the right choice by users because it provides various features that are not found in other music player applications, especially for regional music applications. Then proceed with the design of the application which will be made using the android studio software. The resulting application is expected to become a popular application among users because this application is the latest application with complete features. The developed application can also be run when it is online or offline.